Solid electrolyte and applied lithium ion battery

By using the multi-doped LixTiyMm(PO4)3 in lithium-ion batteries, the concentration of titanium ions is reduced, the redox reaction between titanium ions and lithium metal is suppressed, the problem of solid electrolyte deterioration is solved, and the stability and cycle life of the battery are improved.

CN119230923APending Publication Date: 2024-12-31CYNTEC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500579.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-27
Filing Date
2024-10-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the discharge process, the solid electrolyte in lithium-ion batteries has structural damage due to the oxidation and reduction reaction between titanium ions and lithium metal, which affects the battery cycle life. The existing oxide-type solid electrolytes have deterioration problems in this regard.

Method used

The multi-doped material LixTiyMm(PO4)3 is used as the solid electrolyte, where M represents at least three different doping elements, the ion valence of the doping element is between +3 and +6, and the ion radius is not greater than 100pm. The content of heterogeneous elements is at least twice that of the titanium component to reduce the concentration of titanium ions, inhibit the redox reaction between titanium ions and lithium metal, and maintain high ionic conductivity.

Benefits of technology

It effectively suppresses the reaction between titanium ions and lithium metal, delays or eliminates the deterioration process of solid electrolytes, improves the charging and discharging efficiency and stability of lithium-ion batteries, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230923A_ABST
    Figure CN119230923A_ABST
Patent Text Reader

Abstract

The invention relates to a solid electrolyte and an applicable lithium ion battery, the solid electrolyte comprises a multi-element doped material, the chemical formula of the multi-element doped material is LixTiyMm (PO4) 3, x is more than or equal to 0.8 and less than or equal to 1.5, 0 lt; m represents at least three different doping elements, m is more than or equal to 1.2 and less than or equal to 1.7, y / m is less than or equal to 0.5, the negative electrode in the lithium ion battery at least comprises a lithium-containing material, and the solid electrolyte is positioned between the positive electrode and the negative electrode of the lithium ion battery and is in contact with the lithium-containing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The present invention relates to a solid electrolyte, in particular to an oxide-type solid electrolyte used in lithium-ion batteries and the lithium-ion batteries using the same. Background Art Today, rechargeable lithium-ion batteries have developed into important energy storage devices with a wide range of applications, such as wearable electronic devices, consumer electronic products, electric vehicles, etc. They have the advantages of high energy density, long life and low price. Using solid electrolytes to replace liquid electrolytes in traditional lithium-ion batteries has the following advantages: high safety, no leakage pollution, no flammable and volatile electrolytes, short circuit prevention, simple preparation, small size, convenient storage, etc., so it has become an important research direction. Solid electrolytes can be initially divided into polymer type, sulfide type, and oxide type. Among them, polymer type such as polyethylene oxide (PEO) or polyacrylonitrile (PAN) has the disadvantages of low ionic conductivity, narrow electrochemical window, low mechanical strength, etc.; sulfide type such as thio-lithium superionic conductor (thio-LISICON), lithium argyrodite or lithium germanium phosphorus sulfur (LGPS) is sensitive to water vapor and easily produces toxic hydrogen sulfide; relatively speaking, oxide type has better advantages in high ionic conductivity and chemical stability, so in the application of portable terminal products, lithium-ion batteries using oxidized solid electrolytes will be a relatively good choice. Sodium superionic conductor (Na superionic conductor; NASICON) has better ionic conductivity and is not sensitive to water vapor and carbon dioxide in the air, so the mass production conditions are relatively low. 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , LATP) material as an example, see Figure 1 During the discharge process, the titanium ions (Ti 4+ ) will produce a redox reaction with the lithium metal of the lithium-ion battery negative electrode 11 (Ti 4+ →Ti 3+) During the charge and discharge process of a lithium-ion battery, as titanium ions (IV) are gradually consumed, the solid electrolyte 13 gradually deteriorates from the surface, and the lithium dendrites deposited after the reduction of lithium ions also penetrate into the structure ( Figure 2 ) causing the structure to be damaged or severely fragmented, affecting the cycle life of the battery. This phenomenon urgently needs to be improved. Summary of the Invention The present invention provides a solid electrolyte suitable for use in a lithium-ion battery. The negative electrode of the lithium-ion battery includes at least a lithium-containing material. The solid electrolyte includes a multi-doped material with the chemical formula Li x Ti y M m (PO 4 ) 3 , where 0.8 ≤ x ≤ 1.5, 0 < y ≤ 0.6, M represents at least three different doping elements, 1.2 ≤ m ≤ 1.7, and y / m ≤ 0.5. In one embodiment, the multi-doped material has a disordered sublattice. In one embodiment, M represents at least four different doping elements. In one embodiment, the multi-doped material is a high-entropy NASICON-type material. In one embodiment, the doping elements are metal elements with an ionic valence between +2 and +6, and more preferably between +3 and +6. In one embodiment, the ionic radius of the doping elements is not greater than 100 pm, and more preferably between 53 pm and 90 pm. In one embodiment, the doping elements are magnesium, aluminum, calcium, scandium, vanadium, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, indium, tin, antimony, hafnium, tantalum, or tungsten. In one embodiment, the ionic conductivity of the solid electrolyte is higher than 10 -5 S·cm -1 . The present invention further provides a lithium-ion battery, including a positive electrode, a negative electrode with a lithium-containing material, and the above-mentioned solid electrolyte. The solid electrolyte is located between the positive electrode and the negative electrode and is in contact with the lithium-containing material. In one embodiment, the negative electrode includes lithium metal or lithium titanate. In one embodiment, the positive electrode includes lithium iron phosphate, lithium manganate, lithium nickel cobalt manganese oxide, or lithium nickel cobalt aluminum oxide. To better understand the above and other aspects of the present invention, the following specific embodiments are given and described in detail in conjunction with the accompanying drawings: Brief Description of the Drawings Figure 1Schematic diagram of the reduction of titanium ions of LATP by lithium metal during battery discharge. Figure 2 Schematic diagram showing the degradation of the solid-state electrolyte LATP after contact with lithium metal. Figure 3A and 3B The present invention is respectively 1.3 Al 0.4 Ti 0.5 Zr 0.5 Sn 0.5 Ta 0.1 (PO 4 ) 3 And the cyclic voltammetry curve measured with known LATP. Figures 4A to 4D 1 is a cyclic voltammetry curve of the multi-doped material according to an embodiment of the present invention. Figure 5A and 5B Schematic diagrams illustrating the diffusion channels of lithium ions between ordered and disordered sublattices, respectively. Figure 6 FIG. 4 is an exploded view of a lithium-ion battery according to an embodiment of the present invention.

Explanation of symbols

[0001] 11: Negative electrode (lithium metal) 13: Solid electrolyte (LATP) 31: Reduction Peak 32: Oxidation peak 51: Negative electrode 52: Positive electrode 53: Solid electrolyte 55: Diffusion channel 60: Lithium-ion battery 67: Shrapnel 68: Gasket 511: Lithium-ion 531: Oxygen Anion Sublattice 532: Titanium cation sublattice 533: Metal Cation Sublattice 661: Top cover 662: Bottom cover DETAILED DESCRIPTION Some specific embodiments are selected below to illustrate the implementation of the present invention. People familiar with the art can clearly understand the technical features and effects of the present invention from the contents disclosed in this specification. However, it should be noted that the structures, proportions, sizes, etc. illustrated in the drawings attached to this specification are only used to match the contents disclosed in the specification for people familiar with the art to understand and read, and are not used to limit the conditions under which the present invention can be implemented. The present invention provides a solid electrolyte suitable for lithium-ion batteries, which includes a multi-element doping material. By replacing part of the titanium component in the solid electrolyte with doping elements, the concentration of titanium (IV) ions is reduced, and the oxidation-reduction reaction between titanium (IV) ions and lithium-containing materials at the negative electrode of the battery is inhibited or prevented, thereby slowing down or eliminating the deterioration process of the solid electrolyte. However, the multi-element doping material still needs to maintain a better ionic conductivity to ensure the charging and discharging efficiency of the lithium-ion battery. According to the present invention, the chemical formula of the multi-doped material is Li x Ti y M m (PO 4 ) 3 , where 0.8≤ lithium content x≤1.5, 0< titanium content y≤0.6, M indicates at least three different doping elements in addition to titanium, 1.2≤ doping element content m≤1.7, the content of the substituted doping element is at least twice the remaining titanium content (y / m ≤0.5), or can be three or four times or more, and the above contents are all expressed in moles. Under the condition of maintaining better ionic conductivity and similar lattice structure, the selection conditions of doping elements are as follows: select metal elements with ionic valence similar to titanium, so that the doped metal elements are more stable in the crystal structure. The ionic valence of titanium (IV) is +4, so the ionic valence of the selected metal elements should be between +2 and +6, or closer to between +3 and +6; select metal elements with ionic radius similar to titanium. If the difference in ionic radius is too large, the precipitation of impurities is likely to occur during the preparation process. The ionic radius of titanium (IV) is 67pm, so the ionic radius of the metal element can be selected to be no more than 100pm, or closer to between 53pm and 90pm. Through the above selection, the position of titanium atoms in the crystal lattice can be replaced more effectively, thereby reducing the titanium content in the material. According to the above selection conditions, the doping elements that can be selected are, for example: magnesium (Mg, +2 ion radius 72pm), aluminum (Al, +3 ion radius 53pm), calcium (Ca, +2 ion radius 100pm), scandium (Sc, +3 ion radius 74.5pm), vanadium (V, +2 ion radius 64pm, +4 ion radius 58pm, +5 ion radius 54pm), zinc (Zn, +2 ion radius 74pm), gallium (Ga, +3 ion radius 62pm), germanium (Ge, +2 ion radius 73pm, +4 ion radius 53pm), yttrium (Y, +3 ion radius 90pm), zirconium (Zr, +4 ion radius 72pm), niobium (Nb, +3 ion radius 72pm, +4 ion radius 68pm, +5 ion radius 64pm), molybdenum (Mo, +3 ion radius 69pm, +4 ion radius 65pm, +5 ion radius 61pm, +6 ion radius 59pm), indium (In, +3 ion radius 80pm), tin (Sn, +4 ion radius 69pm), antimony (Sb, +3 ion radius 76pm, +5 ion radius 60pm), hafnium (Hf, +4 ion radius 71pm), tantalum (Ta, +3 ion radius 72pm, +4 ion radius 68pm, +5 ion radius 64pm), tungsten (W, +4 ion radius 66pm, +5 ion radius 62pm, +6 ion radius 60pm), etc. When selecting, it is possible to consider selecting metal elements with less valence changes to avoid the formation of multiphase products and the need for subsequent complex separation steps, thereby increasing the possibility that the product is a single thermodynamic product and improving the purity and yield of a specific single product. At least three or more doping elements can be selected to prepare Li x Ti y M1 m1 M2 m2 M3 m3 (PO 4 ) 3 , Li x Ti y M1 m1 M2 m2 M3 m3 M4 m4 (PO 4 ) 3 Etc. or even more doping elements are used to reduce the titanium component of the multi-doped material. The values ​​of m1, m2, m3, m4... will change due to charge balance. For example, when high-valent and low-valent elements are used for doping at the same time, the proportion of high-valent elements in the material can be slightly reduced. Finally, the total content m of the doping elements is between 1.2 and 1.7. The synthesis method used can be a wet chemical method (such as a sol-gel method, a co-precipitation method), a melt-quenching method, a solid phase method and other known methods, but is not limited thereto. Several embodiments are given below to illustrate the properties of the multi-doped material of the present invention. In one embodiment, the doping elements selected are aluminum (III), zirconium (IV), tin (IV), and tantalum (V). The synthesized multi-doped material has a NASICON crystal phase through X-ray diffraction (XRD) identification and spectrum comparison. The scanning electron microscope (SEM) and energy-dispersive X-ray spectroscopy (EDS) observation and analysis show that the composition is Li 1.3 Al 0.4 Ti 0.5 Zr 0.5 Sn 0.5 Ta 0.1 (PO 4 ) 3 The molar ratio of titanium to doping element is 0.33 (y / m = 0.5 / 1.5 = 0.33), that is, the content of doping element is three times that of titanium, and the measured ionic conductivity is 1.32×10 -4 S cm -1 The redox behavior of the metal and lithium metal at a set voltage was measured by cyclic voltammetry (scan rate 1 mV / s). The obtained cyclic voltammetry curve is as follows: Figure 3A As shown, Figure 3B Compared with the LATP material of the present invention, the LATP material will have an obvious reduction peak (cathodic peak) 31 at 2.2V, at which time the titanium ion (IV) is reduced to titanium ion (III), and the oxidation peak (anodic peak) 32 is lower than the reduction peak 31, so the titanium ion (IV) will gradually lose and deteriorate the LATP material. On the contrary, the Li 1.3 Al 0.4 Ti 0.5 Zr 0.5 Sn 0.5 Ta 0.1 (PO 4 ) 3 No obvious reduction reaction was measured at 2.2V, which shows that the reaction between titanium (IV) ions and lithium metal can be effectively inhibited and the stability of the solid electrolyte to lithium metal is improved, so it is suitable for lithium-ion batteries. In other embodiments, aluminum (III), zirconium (IV), yttrium (III), niobium (III), tantalum (V), tungsten (VI) and the like are used to prepare other multi-element doping materials. 0.4 Ti 0.4 Y 0.4 Zr 0.4 W 0.4 (PO 4 )3 、LiAl 0.4 Ti 0.4 Zr 0.4 Nb 0.4 W 0.4 (PO 4 ) 3 , Li 1.4 Al 0.4 Ti 0.4 Y 0.4 Zr 0.4 Ta 0.4 (PO 4 ) 3 , Li 1.4 Al 0.4 Ti 0.4 Zr 0.4 Nb 0.4 Ta 0.4 (PO 4 ) 3 The doping element content of these multi-doped materials is four times that of titanium (y / m = 0.5 / 1.5 = 0.25), and their XRD spectra show a NASICON crystal phase with an ionic conductivity of nearly 10 -5 S cm -1 , and their cyclic voltammetry curves are as follows Figures 4A to 4D As shown in the figure, no obvious reduction reaction was measured at 2.2V, which proves that the reaction between titanium ion (IV) and lithium metal can be effectively inhibited; in addition, the difference between the redox peak pair of LATP material is 1.04V ( Figure 3B ), and in the small amount of redox reaction of the multi-doped material prepared here, the difference of the redox peak pair is about 1.35V to 2.4V. The enlarged difference indicates that the reduction reaction of titanium ion (IV) is delayed, and it also has an inhibitory effect, which shows that the stability of the solid electrolyte to lithium metal is improved, and thus it is suitable for lithium-ion batteries. The present invention is not limited to NASICON type materials. For example, the multi-doped materials obtained by doping with the above-mentioned appropriate ions may be suitable for use in lithium-ion batteries even if they do not show a NASICON crystal phase, provided that they have better stability to lithium metal and suitable ionic conductivity. The above-mentioned multi-doped materials can be well adhered to the lithium metal negative electrode, without the need to add an additional protective layer between the solid electrolyte and the lithium metal, and are also insensitive to moisture and carbon dioxide in the air. Therefore, they have more advantages in production process and cost. Please note that the multi-doped materials according to the concept of the present invention are not limited to the specific materials listed above. According to the concept of the present invention, by using the high-entropy doping method, a variety of specific elements are mixed into the material to form disorder and tend to form the thermodynamically most stable product, making the product single and stable, and less likely to have intermediate phases, so that a relatively pure-phase crystal product can be prepared. Please refer to Figure 5A and Figure 5B , which are schematic diagrams respectively showing the transmission channels of lithium ions between ordered and disordered sublattices. In Figure 5A , within the solid electrolyte 53 between the negative electrode 51 and the positive electrode 52, the oxygen anion sublattice 531 and the titanium cation sublattice 532 are arranged in an ordered manner, and a lithium ion diffusion channel 55 is formed therebetween; in Figure 5B , because the titanium cation sublattice 532 in the solid electrolyte 53 and the other doped metal cation sublattices 533 have different sizes, the oxygen anion sublattice 531 and the titanium cation sublattice 532 / metal cation sublattices 533 are arranged in a disordered manner, expanding some of the lithium ion diffusion channels 55, enabling the lithium ions 511 to be transmitted more quickly, thus increasing the ionic conductivity. The present invention also provides a all-solid-state lithium-ion battery 60. Please refer to Figure 6 , which is an exploded view of the components of the lithium-ion battery according to an embodiment of the present invention. The main structure includes a negative electrode 51, a positive electrode 52, and a solid electrolyte 53. The negative electrode 51 includes at least one lithium-containing material. The solid electrolyte 53 is located between the positive electrode 52 and the negative electrode 51 and is in contact with the lithium-containing material. The solid electrolyte 53 pressed into a pellet shape includes a multi-doped material, and its chemical formula is Li x Ti y M m (PO 4 ) 3 , where 0.8 ≤ x ≤ 1.5, 0 < y ≤ 0.6, M represents at least three different doping elements, 1.2 ≤ m ≤ 1.7, y / m ≤ 0.5. The details are as described above. Any of the aforementioned multi-doped materials can be used and will not be elaborated here. In one embodiment, the negative electrode 51 can use lithium metal or lithium titanate (Li 4 Ti 5 O 12 ), and the positive electrode 52 can use lithium iron phosphate (LiFePO 4 , LFP), lithium manganate (LiMn 2 O 4 ), lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA), etc., but not limited thereto. The lithium-ion battery 60 of the present invention can be applied to different shapes. Figure 6An example is shown, in which the combination of the negative electrode 51, the solid electrolyte 53, and the positive electrode 52 is placed in the accommodation space between the top cover 661 and the bottom cover 662, and the spring 67 and the gasket 68 are added to fix their relative positions. The resulting lithium-ion battery uses a solid electrolyte that is stable to lithium-containing materials and insensitive to water vapor / carbon dioxide. It does not require an additional protective layer, which can improve durability, simplify the process and reduce production costs. Its good ionic conductivity can also enable the lithium-ion battery to have sufficient charging and discharging efficiency. In summary, although the present invention has been disclosed as above by way of embodiments, it is not intended to limit the present invention. A person having ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the scope of the attached patent application.

Claims

1. A solid electrolyte for use in a lithium-ion battery, wherein a negative electrode of the lithium-ion battery comprises at least a lithium-containing material, characterized in that: The solid electrolyte includes a multi-doped material with a chemical formula of Li x Ti y M m (PO4)3, where 0.8 ≤ x ≤ 1.5, 0 < y ≤ 0.6, M represents at least three different doping elements, 1.2 ≤ m ≤ 1.7, and y / m ≤ 0.

5.

2. The solid electrolyte of claim 1, wherein the multi-doped material has a disordered sub-lattice.

3. The solid electrolyte of claim 1, wherein M represents at least four different doping elements.

4. The solid electrolyte as claimed in claim 3, wherein the multi-doped material is a high entropy NASICON type material.

5. The solid electrolyte as claimed in claim 1, wherein each of the doping elements is a metal element, and its ion valence is between +2 and +6.

6. The solid electrolyte as claimed in claim 5, wherein the ion valence of the metal element is between +3 and +6.

7. The solid electrolyte as claimed in claim 1, wherein the ion radius of each of the doping elements is not greater than 100 pm.

8. The solid electrolyte of claim 7, wherein the ionic radius is between 53 pm and 90 pm.

9. The solid electrolyte of claim 1, wherein each of the doping elements is selected from magnesium, aluminum, calcium, scandium, vanadium, zinc, gallium, germanium, yttrium, zirconium, niobium, molybdenum, indium, tin, antimony, hafnium, tantalum and tungsten.

10. The solid electrolyte as claimed in claim 1, wherein the ionic conductivity of the solid electrolyte is higher than 10 -5 S cm -1 .

11. A lithium ion battery, characterized in that: include: A positive electrode; a negative electrode comprising at least one lithium-containing material; as well as The solid electrolyte according to any one of claims 1 to 10, wherein the solid electrolyte is located between the positive electrode and the negative electrode and is in contact with the lithium-containing material.

12. The lithium ion battery of claim 11, wherein the negative electrode comprises lithium metal or lithium titanate. 13 . The lithium-ion battery as claimed in claim 11 , wherein the positive electrode comprises lithium iron phosphate, lithium manganese oxide, lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide.